Martha Nussbaum, Essentialism, and Human Sexuality - Ball, Carlos A. (Columbia Journal of Gender and Law, 2010)
It is an honor to participate in this program recognizing the work of Professor Martha Nussbaum. A few years ago, after being fortunate enough to have been awarded tenure, the university library at the institution where I worked at the time asked me to choose a book I valued for an exhibit of books chosen by recently tenured professors. I chose Nussbaum’s Women and Human Development, a book that has had a deep intellectual influence on me.’ One of the chapters in that book is titled “In Defense of Universal Values,” a topic that is relevant to this Article. Critiques of essentialism are a common theme in the writings of many contemporary academics. Indeed, queer theorists, critical race theorists, post-structuralists, post-colonialists, and many feminists consistently take issue with the notion that there are attributes or traits that are intrinsically constitutive of categories such as men and women, heterosexuals and homosexuals, disabled and non-disabled, and so on.2 The emphases and nuances of the anti-essentialist critiques differ depending on membership in particular academic camps and disciplines. However, the critiques uniformly reject moral, philosophical, and political understandings that are explicitly or implicitly grounded in the notion that identities-and for some critics, even the very idea of a “human being”-are static and fixed, that is, immune or separate from forces of social construction. Anti- essentialist critiques hold instead that much (or all) of what constitutes us as individuals is socially constructed and therefore fluid and contestable.